2021
DOI: 10.1002/lpor.202100255
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Transition Metal Dichalcogenides for High Power Vector Dissipative Soliton Ultrafast Fiber Laser

Abstract: 2D ternary transition metal dichalcogenides (TMDCs) have been studied widely by researchers from the fields of nanotechnology to materials science because of the extraordinary chemical/physical characteristics, and significant potential in nanoscale device applications. Here, the application of Nb x Re (1−x) S 2 nanosheets in ultrafast photonics is studied. The few-layer Nb x Re (1−x) S 2 nanosheets are fabricated through liquid phase exfoliation method and a Nb x Re (1−x) S 2 -microfiber device is constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(40 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Many studies examining ultrafast fiber lasers based on 2D TMDs as SAs have been reported [ 34 , 35 , 36 , 37 ]. However, TMDs devices are not suited for the mid-infrared region, since the intrinsic energy bandgap of TMDs is limited from 1 to 2 eV [ 38 ]. BP has attracted great interest in both potential applications and academic research recently, benefiting from its remarkable characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examining ultrafast fiber lasers based on 2D TMDs as SAs have been reported [ 34 , 35 , 36 , 37 ]. However, TMDs devices are not suited for the mid-infrared region, since the intrinsic energy bandgap of TMDs is limited from 1 to 2 eV [ 38 ]. BP has attracted great interest in both potential applications and academic research recently, benefiting from its remarkable characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the addition of the third element owing to their unique structure and remarkable physical and chemical properties endow these materials with considerable potential for applications in nanoscale devices. Re x Nb (1−x) S 2 -based saturable absorber (SA) and Nb x Re (1−x) S 2 nanosheets are the examples that have been used for SA in the generation of ultrashort pulses in EDF laser cavity [16,17]. Recently, Liu et al demonstrated the soliton mode-locked using a tapered fiber based saturable absorber as an enhancement to nonlinearity with different thickness of Y 2 O 3 layer, namely 5 nm, 8 nm, and 20 nm acting as a material for an ultrafast laser generation [18].…”
Section: Introductionmentioning
confidence: 99%
“…High‐performance glass fiber laser has gained increasing attention due to its unique superiorities, including high beam quality, adequate reliability, and good heat dissipation, showing potential applications in material processing, optical communication, nonlinear optics, and quantum optics 1–4 . Compared with a continuous wave (CW) fiber laser, ultrashort pulsed fiber laser with high peak power, high output energy, high repetition frequency, and wide frequency spectrum has attracted great attention because of its widespread applications in micromachining, optical information processing, biomedicine, and spectroscopy 5–8 . The ultrafast laser operating at ∼1 µm is located in the near‐infrared‐Ⅱ biological window (900–1700 nm) and has low optical attenuation for most biological specimens; thus it can increase two‐photon excitation imaging rate to obtain high contrast image in deep specimens 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Compared with a continuous wave (CW) fiber laser, ultrashort pulsed fiber laser with high peak power, high output energy, high repetition frequency, and wide frequency spectrum has attracted great attention because of its widespread applications in micromachining, optical information processing, biomedicine, and spectroscopy. [5][6][7][8] The ultrafast laser operating at ∼1 µm is located in the near-infrared-II biological window (900-1700 nm) and has low optical attenuation for most biological specimens; thus it can increase two-photon excitation imaging rate to obtain high contrast image in deep specimens. 9 Among the active centers, rare-earth (RE) ion Yb 3+ can achieve efficient ∼1-µm laser output because of the 2 F 5/2 → 2 F 7/2 transition.…”
Section: Introductionmentioning
confidence: 99%